Electrophotographic member, electrophotographic processing cartridge, electrophotographic image forming device, and copolymer

JP2025030318APending Publication Date: 2025-03-07CANON KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023135496
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0009】 本開示の少なくとも一の態様によれば、低温環境下における高品位な電子写真画像の安定的な形成に資する電子写真部材を得ることができる。また、本開示の少なくとも一の態様によれば、高品位な電子写真画像の安定的な形成に資する電子写真プロセスカートリッジを得ることができる。また、本開示の少なくとも一の態様によれば、高品位な電子写真画像を安定して形成することができる電子写真画像形成装置を得ることができる。さらに、本開示の少なくとも一の態様によれば、イオンの効果的な解離に資する共重合体を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an electrophotographic member for forming high-quality images.SOLUTION: An electrophotographic member provided herein contains a compound having a structure represented by a formula (1) and a structure represented by a formula (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrophotographic member incorporated in an apparatus employing an electrophotographic system, an electrophotographic process cartridge and an electrophotographic image forming apparatus using the electrophotographic member, and a copolymer. [Background technology]

[0002] In an electrophotographic image forming apparatus (also called an "electrophotographic apparatus"), electrophotographic members having a conductive layer are used as, for example, a developing member, a charging member, a toner supplying member, and a cleaning member. The conductive layer of the electrophotographic member has, for example, an electrical resistance value of 1.0×10 5 ~1.0×10 9 The conductivity is controlled within the Ω range. The conductivity must be uniform throughout the entire member and stable over time. Conductive agents used to impart a specific conductivity to the conductive layer include conductive particles such as carbon black, and ionic conductive agents such as salt compounds of sulfonylimide anions and metal cations.

[0003] An electronically conductive roller to which conductive particles such as carbon black are added has the advantage that even when electricity is applied for a long period of time, changes such as high resistance due to uneven distribution of conductive components are unlikely to occur. On the other hand, however, it is difficult to uniformly disperse conductive particles such as carbon black, and localized areas of high or low resistance may occur. Compared to electronically conductive rollers, an ionically conductive roller to which an ionically conductive agent is added can reduce unevenness in electrical resistance caused by uneven dispersion of the conductive agent, and is unlikely to produce localized areas of high or low resistance. Therefore, in the developing roller, the developer can be developed uniformly on the photoconductor, and in the charging roller, the surface of the photoconductor can be uniformly charged.

[0004] Patent Document 1 discloses a conductive roller formed using a polymer composition that contains a non-chlorine / non-bromine polymer as a main component and a salt having an anion having a fluoro group and a sulfonyl group. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-163825 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, electrophotographic devices are required to maintain high image quality and high durability even under harsher environments. The present inventors mounted the conductive roller described in Patent Document 1 as a developing roller in an electrophotographic process cartridge, and output a large number of electrophotographic images in an environment at a temperature of 0° C. using this process cartridge. As a result, as the number of output sheets increased, the occurrence of ghosts in the electrophotographic images was sometimes observed.

[0007] At least one aspect of the present disclosure is directed to providing an electrophotographic member that contributes to the stable formation of high-quality electrophotographic images in a low-temperature environment. At least one aspect of the present disclosure is directed to providing an electrophotographic process cartridge that contributes to the stable formation of high-quality electrophotographic images. At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. Furthermore, at least one aspect of the present disclosure provides a copolymer that is conducive to efficient dissociation of ions. It is intended for children. [Means for solving the problem]

[0008] According to one aspect of the present disclosure, 1. An electrophotographic member having an electrically conductive substrate and an electrically conductive layer on the substrate, An electrophotographic member is provided, wherein the conductive layer comprises a compound having a structure represented by the following formula (1) and a structure represented by the following formula (2): [ka] [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, A1 represents a linking group having a structure represented by (-CH2CH2-O-). In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms, R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms, X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. Effect of the Invention

[0009] According to at least one aspect of the present disclosure, an electrophotographic member contributing to the stable formation of a high-quality electrophotographic image in a low-temperature environment can be obtained. According to at least one aspect of the present disclosure, an electrophotographic process cartridge contributing to the stable formation of a high-quality electrophotographic image can be obtained. According to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming a high-quality electrophotographic image can be obtained. Furthermore, according to at least one aspect of the present disclosure, a copolymer contributing to effective dissociation of ions can be obtained. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of an example of an electrophotographic roller according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic configuration diagram of an example of a process cartridge according to an embodiment of the present disclosure. [Diagram 3] 1 is a schematic cross-sectional view of an example of an electrophotographic apparatus according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic diagram of a jig for evaluating the resistance value of a developing roller. [Diagram 5] FIG. 1 is an image diagram showing a mechanism according to one embodiment of the present disclosure. [Figure 6] 1 is a schematic cross-sectional view of an example of a blade member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0012] The present inventors confirmed that the electrical resistance of the surface of the conductive roller increased immediately after the occurrence of a ghost image in an output test of an electrophotographic image in a low-temperature environment using the conductive roller according to the above-mentioned Patent Document 1. From this, they speculated that the occurrence of the ghost image was caused by the accumulation of electric charge on the conductive roller as the number of output sheets of electrophotographic images increased. Based on these considerations, the present inventors have conducted extensive research and have found that the following electrophotographic member contributes to solving the above-mentioned problems.

[0013] That is, the electrophotographic member according to one aspect of the present disclosure is 1. An electrophotographic member having an electrically conductive substrate and an electrically conductive layer on the substrate, The conductive layer contains a compound having a structure represented by the following formula (1) and a structure represented by the following formula (2): [ka] [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4), R 3 represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 1), A1 represents a linking group having a structure represented by (-CH2CH2-O-). In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms (preferably 2 to 4), R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms (preferably 1 to 2), X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion.

[0014] The present inventors speculate as follows why the electrophotographic member having the above-mentioned configuration is unlikely to cause ghosts even when used to form a large number of electrophotographic images in a low-temperature environment.

[0015] Generally, compounds containing chemical species with strong Lewis acidity or Lewis basicity form crystals (ionic crystals) due to their strong electrostatic interactions. In this case, the compound alone does not undergo ionic dissociation. In order to develop electrical conductivity in such a compound, it is necessary to dissociate the anion and cation. For this purpose, it is effective to add water to solvate the cation and stabilize it. Thus, in order to dissociate a compound that exhibits strong electrostatic interactions, it is necessary to stabilize the dissociated chemical species.

[0016] Metal cations have a smaller ionic radius and higher mobility than organic cations. Therefore, even if they are polarized by current when a voltage is applied, they are expected to diffuse quickly and uniformly when the voltage is released. Therefore, they are less likely to become highly resistive due to degradation caused by current flow, making them ideal.

[0017] Patent Document 1 relates to a technique of coexisting a polyether-containing polymer or a polymer having a cyan group with a salt having an anion having a fluoro group and a sulfonyl group. In this document, the counter cation of the above anion is lithium. Lithium is a strong Lewis acidic ion species and exhibits strong ionic bonding, so it is difficult to dissociate and has low conductivity by itself. For this reason, the document discloses an idea of ​​stabilizing the cation generated by dissociation with a molecule having an electron-rich functional group, thereby promoting dissociation and improving conductivity.

[0018] On the other hand, in an image output test conducted by the present inventors, when images were output to the end in a low-temperature environment such as 0°C, the developing roller was found to have a high resistance. This is thought to be due in part to the fact that the structures for stabilizing cations are not spatially close to each other due to the decrease in molecular mobility caused by the low temperature. In addition, even if they are spatially close to each other, not only the cations but the entire ionic molecule is attracted to each other, and as a result, dissociation of the ions does not occur. To solve the above problems, a conductive agent that satisfies the following conditions (i) and (ii) is considered to be effective. (i) The structures that stabilize the cations are in close spatial proximity. (ii) The anion remains in place while the cation is pulled away.

[0019] The present inventors have investigated the molecular structure of a compound that satisfies the conditions (i) and (ii), and have found that a suitable function can be obtained by including a compound having a structure represented by the above formula (1) and a structure represented by the above formula (2). In the compound having the structure represented by the formula (1) and the structure represented by the formula (2), the sulfonylimide anion and metal cation, which are ionic components, and the ether structure, which is expected to stabilize the cation, coexist in the same molecule. In addition, since the ionic component is fixed to the tip of the acrylic structure, when the ether component attracts the cation, the ionic component is fixed to the tip of the acrylic structure. It is presumed that the anions are not attracted to each other and that ions are dissociated effectively (see the image in Figure 5). Furthermore, when a copolymer having a structure represented by the above formula (1) and a structure represented by the above formula (2) is contained as a copolymerization component, even more preferable functions can be obtained. An example of the copolymer having the structure represented by formula (1) and the structure represented by formula (2) is a vinyl copolymer described below.

[0020] <<Ionic Conductive Agent>> The ionic conductive agent according to the present disclosure includes a compound having a structure represented by formula (1) and a structure represented by formula (2), and more preferably includes a compound (preferably a copolymer) having a structure represented by formula (1) and a structure represented by formula (2).

[0021] In addition, it is preferable that A1 in the formula (1) further has a structure represented by (-CH2-CH(CH3)-O-). The structure represented by the formula (1) is more preferably a structure represented by the following formula (1-1). [ka] R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 2 to 4), R 3 represents an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4, more preferably 1), m1 and n1 are the average number of moles added, where m1 represents an integer of 1 or more (preferably 1 to 110, more preferably 13 to 46), and n1 represents an integer of 0 or more (preferably 5% to 25% of m1, more preferably 11% to 25% of m1). However, the arrangement of the structure represented by (-CH2-CH2-O-) and the structure represented by (-CH2-CH(CH3)-O-) may be a block copolymer or a random copolymer. When the compound is a copolymer, the number average molecular weight (Mn) of the copolymer is preferably 500 to 100,000 (more preferably 1,000 to 50,000) from the viewpoint of the balance between bleed-out and compatibility. From the viewpoint of realizing the above-mentioned mechanism, the molar ratio of the structure represented by formula (1) to the structure represented by formula (2) in the copolymer (the structure represented by formula (1):the structure represented by formula (2)) is preferably 60:40 to 95:5, and more preferably 75:25 to 90:10. The content of the compound having the structure represented by formula (1) and the structure represented by formula (2) in the conductive layer is preferably 0.50% by mass to 5.0% by mass, and when the conductive layer contains a binder resin, the content is preferably 1.0 part by mass to 5.0 parts by mass with respect to the binder resin.

[0022] In order to obtain the compound used in the ion conductive agent according to the present disclosure, the following raw materials can be used. Polyether mono(meth)acrylate Sulfonylimide ionic compounds with unsaturated reactive functional groups

[0023] [Polyether mono(meth)acrylate] The polyether mono(meth)acrylate can form a structure represented by formula (1) (preferably formula (1-1)). As the polyether mono(meth)acrylate, for example, at least one selected from the group consisting of polyethylene glycol mono(meth)acrylate and mono(meth)acrylate of polyethylene glycol-propylene glycol copolymer can be used. When the mono(meth)acrylate of polyethylene glycol-propylene glycol copolymer is used, the molar ratio of ethylene glycol structure:propylene glycol structure is preferably 100:0 to 50:50, more preferably 80:20 to 95:5. When the molar ratio of the ethylene glycol structure to the propylene glycol structure is within this range, the lithium ion X of the polyethylene glycol + The ion transportability represented by the formula (I) can be maintained at a high level.

[0024] The polyether mono(meth)acrylate is represented, for example, by the following formula (1'). [ka] The structure represented by formula (1) (preferably formula (1-1)) can be obtained, for example, by using a polyether polyol obtained by ring-opening polymerization of ethylene oxide and propylene oxide. In formulas (1-1) and (1'), the arrangement of the ethylene oxide structure represented by (-CH2-CH2-O-) and the propylene oxide structure represented by (-CH2-CH(CH3)-O-) may be a block copolymer or a random copolymer. Random copolymerization is preferred.

[0025] The polyether mono(meth)acrylate may be synthesized by a known method, or a commercially available product may be used. For example, a known method is to add ethylene oxide / propylene oxide to an alcohol as a starting material to obtain a polyether monool, which is then reacted with (meth)acrylic acid to obtain a polyether mono(meth)acrylate.

[0026] [Sulfonylimide anion group] The ionic conductive agent according to the present disclosure is characterized in that it contains a compound having the structure represented by the above formula (2) in its structure. Examples of compounds capable of forming the structure represented by formula (2) include sulfonylimide ionic compounds having an unsaturated reactive functional group, represented by the following formulae C-1 to C-8. [ka] [ka] The above ionic compounds can be obtained by synthesis using known methods.

[0027] By reacting the above-mentioned polyether mono(meth)acrylate with a sulfonylimide-based ionic compound having an unsaturated reactive functional group, a compound having a structure represented by the formula (1) and a structure represented by the formula (2) can be obtained. The content of the structure represented by formula (2) in the structure of the compound is preferably 20 to 80 parts by mass, and particularly preferably 30 to 70 parts by mass, per 100 parts by mass of the structure represented by formula (1). When the mass fraction of the structure represented by formula (2) is within this range, a sufficient amount of metal cations is contained while also being abundantly present in the cation stabilizing component, and thus dissociation between ions occurs favorably, which is expected to improve ionic conductivity. The state after these reactions can be confirmed by analysis using known means such as pyrolysis GC / MS, FT-IR, and NMR.

[0028] <Cation> Cation X in formula (2) +Examples of the cation include at least one selected from the group consisting of lithium ion, sodium ion, and potassium ion. Among these cations, lithium ion is particularly preferred because of its small ionic radius and high mobility.

[0029] <<Electrophotographic materials>> An electrophotographic member according to an embodiment of the present disclosure has a conductive substrate and a surface layer provided on the substrate. As an example of an electrophotographic member, a roller-shaped electrophotographic member (electrophotographic roller) is shown in Figs. 1(a) to 1(c). The electrophotographic member 1 shown in Fig. 1(a) is composed of a conductive substrate 2 and a surface layer 3 formed on the outer periphery thereof, the surface layer 3 being a conductive layer containing a compound having a structure represented by formula (1) and a structure represented by the following formula (2). As shown in Fig. 1(b), an elastic layer 4 may be provided between the substrate 2 and the surface layer 3. In addition, as shown in Fig. 1(c), the electrophotographic member 1 may have a three-layer structure in which an intermediate layer 5 is further provided between the elastic layer 4 and the surface layer 3, or may have a multi-layer structure in which a plurality of intermediate layers 5 are provided. The conductive layer may be a resin layer made of a conductive resin.

[0030] The layer structure of the electrophotographic member 1 is not limited to the structure shown in Fig. 1(a) to (c). For example, the electrophotographic member 1 may have a surface layer on the conductive layer provided on the substrate 2 and the conductive layer provided on the substrate 2, and one or more other resin layers or protective layers may be laminated on the conductive layer to form a surface layer. The electrophotographic member 1 may also have a conductive layer as an intermediate layer 5. Among these, in order to further enhance the effects of the present disclosure, the electrophotographic member of the present disclosure preferably has a conductive layer present as the outermost surface layer as the surface layer 3, as shown in Fig. 1(a) to (c). The electrophotographic member 1 preferably has an elastic layer 4.

[0031] The electrophotographic member according to one embodiment of the present disclosure can be used, for example, as a developer carrier, a charging member, a developer supplying / stripping member, a developer regulating member, and a cleaning blade. In particular, it can be suitably used as a developer carrier and a developer regulating member. Hereinafter, the configuration of the electrophotographic member according to one embodiment of the present disclosure will be described in detail.

[0032] <Surface layer> The conductive layer of the electrophotographic member preferably contains a binder resin, and the binder resin more preferably contains an ether structure. A specific embodiment is, for example, a binder resin that is contained in the conductive layer on the outermost surface of the electrophotographic roller. This is because, as mentioned above, the binder resin exhibits the effect of stabilizing metal cations. Furthermore, from the viewpoint of the strength of the electrophotographic member and the rubbing against other members, the binder resin is preferably polyurethane, and particularly preferably crosslinked urethane resin.

[0033] [Cross-linked urethane resin] The crosslinked urethane resin is obtained by forming a urethane group by reacting a polyol having a hydroxyl group with an isocyanate compound. The crosslinking here means that one or both of the raw materials of the urethane resin selected from the group consisting of a polyol and an isocyanate compound have three or more reactive functional groups, resulting in a three-dimensional network structure. Such a crosslinked urethane resin has excellent flexibility and high strength.

[0034] The urethane resin can be obtained from a polyol, an isocyanate compound, and, if necessary, a chain extender. Examples of the polyol that is the raw material for the urethane resin include polyether polyol, polyester polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, and mixtures thereof. Examples of the isocyanate compound that is the raw material for the urethane resin include the following. Tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) , naphthalene diisocyanate (NDI), tolidine diisocyanate (TODI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), cyclohexane diisocyanate and mixtures thereof.

[0035] Optional chain extenders include bifunctional low molecular weight diols such as ethylene glycol, 1,4-butanediol, and 3-methylpentanediol, trifunctional low molecular weight triols such as trimethylolpropane, and mixtures thereof. In addition, prepolymer-type isocyanate compounds having isocyanate groups at the terminals, which are obtained by reacting the above-mentioned various isocyanate compounds with various polyols in advance in a state in which the isocyanate groups are in excess relative to the hydroxyl groups, may be used. In addition, as these isocyanate compounds, materials in which the isocyanate groups are blocked with various blocking agents such as methyl ethyl ketone (MEK) oxime may be used.

[0036] Regardless of which material is used, a urethane resin can be obtained by reacting the polyol with the isocyanate compound by heating. When either or both of the polyol and the isocyanate compound have a branched structure and have three or more functional groups, the obtained urethane resin becomes a crosslinked urethane resin, which is preferable. From the viewpoint of stabilizing the above-mentioned metal cations, it is particularly preferable that either or both of the polyol and the isocyanate compound have an ethylene oxide structure or a propionoxide structure.

[0037] [Other ingredients] In addition to the above, the surface layer may contain conductive substances, crosslinking agents, plasticizers, fillers, extenders, vulcanizing agents, vulcanization aids, crosslinking aids, antioxidants, antiaging agents, processing aids, leveling agents, etc., within the range that does not impair the function of the surface layer. In addition, when surface roughness is required in the surface layer, fine particles for imparting roughness to the surface layer may be contained. Specifically, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, polycarbonate resin, etc. may be used. The volume average particle diameter of the fine particles is preferably 1.0 μm or more and 30 μm or less, and the surface roughness (ten-point average roughness) Rzjis formed by the fine particles is preferably 0.1 μm or more and 20 μm or less. Rzjis is a value measured based on JIS B0601 (1994).

[0038] <Base> The conductive substrate 2 functions as an electrode and a support member for the electrophotographic member 1. The substrate is made of a conductive material such as a metal or alloy, such as aluminum, a copper alloy, or stainless steel; iron plated with chromium or nickel; or a conductive synthetic resin. A primer may be applied to the surface of the substrate in order to improve adhesion between the substrate and the elastic layer described below. Examples of the primer include silane coupling agent primers, urethane, acrylic, polyester, polyether, or epoxy thermosetting resins, and thermoplastic resins. Examples of commercially available primers include the following.

[0039] "DY39-051", "DY39-012", "DY39-115" (all product names, manufactured by Dow Corning Toray Co., Ltd.); "X-33-173", "PRIMER-NO.4", "PRIMER-NO.32", "PRIMER-NO.35" (all trade names, manufactured by Shin-Etsu Chemical Co., Ltd.); "XP81-405", "XP81-A6361", "XP81-B7015", "ME21", "ME151", "ME153", "XC9214" (all product names, (Manufactured by Contive Performance Materials Japan, LLC.)

[0040] To improve the adhesion of the primer, known alkoxysilanes, titanates, etc. may be added. Specific examples of alkoxysilanes and titanates include tetramethoxysilane, tetraethoxysilane, tetra-n-butoxysilane, tetraethoxytitanium, tetraisopropoxytitanium, and tetra-n-butoxytitanium. These are preferably added in an amount of 0.1 to 20 parts by mass per 100 parts by mass of the primer.

[0041] <Elastic layer> The elastic layer 4 has a function of providing the electrophotographic member 1 with the elasticity required to form a nip of a predetermined width at the contact portion between the electrophotographic member 1 and the photoreceptor when the electrophotographic member is in the form of a roller, i.e., when the electrophotographic member is an electrophotographic roller. The elastic layer 4 is preferably a molded body of a rubber material. As the rubber material, various rubber materials conventionally used for conductive rubber rollers can be used. Specific examples of rubbers used for the rubber material include ethylene-propylene-diene copolymer rubber (EPDM), acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), natural rubber (NR), isoprene rubber (IR), styrene-butadiene rubber (SBR), fluororubber, silicone rubber, epichlorohydrin rubber, NBR hydride, polysulfide rubber, and urethane rubber. These may be used alone or in combination of two or more. Among these, silicone rubber is preferable from the viewpoint of stability against deformation, particularly in set performance. Examples of the silicone rubber include polydimethylsiloxane, polymethyltrifluoropropylsiloxane, polymethylvinylsiloxane, polyphenylvinylsiloxane, and copolymers of these polysiloxanes.

[0042] Various additives such as a conductivity imparting agent, a non-conductive filler, a crosslinking agent, and a catalyst may be appropriately blended into the elastic layer 4. As the conductivity imparting agent, carbon black; conductive metals such as aluminum and copper; and fine particles of conductive metal oxides such as zinc oxide, tin oxide, and titanium oxide can be used. Among these, carbon black is preferred because good conductivity can be obtained with a relatively low amount added.

[0043] Specific examples of carbon black that can be used include conductive carbon black such as Ketjen Black (trade name, manufactured by Lion Corporation) and acetylene black; rubber carbon black such as SAF, ISAF, HAF, FEF, GPF, SRF, FT, and MT; and other carbon blacks for color inks that have been subjected to oxidation treatment, and pyrolytic carbon black. These may be used alone or in combination of two or more. When carbon black is used as the conductivity imparting agent, it is more preferable to mix 10 to 80 parts by mass of carbon black with respect to 100 parts by mass of rubber in the rubber material.

[0044] Examples of non-conductive fillers include silica, quartz powder, titanium oxide, zinc oxide, and calcium carbonate. Examples of cross-linking agents include di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and dicumyl peroxide. Examples of catalysts include platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts, with platinum-based catalysts being particularly preferred. The elastic layer 4 may be formed of a plurality of layers. An intermediate layer 5 may be provided between the base 2 and the elastic layer 4, and between the elastic layer 4 and the surface layer 3. The thickness of the elastic layer 4 is preferably 0.25 to 8.00 mm, and more preferably 0.30 to 3.00 mm.

[0045] <<Electrophotographic device>> The electrophotographic member according to the present disclosure is a developer carrier and a developer regulating member in an electrophotographic device. The electrophotographic member can be applied to any of developing devices, including non-contact developing devices and contact developing devices using magnetic one-component toner or non-magnetic one-component toner, and developing devices using two-component toner. FIG. 2 is a schematic cross-sectional view showing an example of an electrophotographic device equipped with an electrophotographic member according to the present disclosure as a developing roller of a contact-type developing device using one-component toner. As shown in FIG. 2, a developing device 22 is detachably mounted on the electrophotographic device. The developing device 22 is composed of a toner container 20 containing toner 15 as one-component toner, a developing roller 16, a toner supply roller 19 supplying toner to the developing roller 16, and a developing blade 21 regulating the thickness of the toner layer on the developing roller 16. The developing roller 16 is located at an opening extending in the longitudinal direction in the toner container 20 and is disposed opposite the photoconductor 18. In addition, a process cartridge 17 composed of the photoconductor 18, a cleaning blade 26, a waste toner container 25, and a charging roller 24 is detachably mounted on the electrophotographic device. The photoconductor 18, the cleaning blade 26, the waste toner container 25, and the charging roller 24 may be disposed in the electrophotographic device main body.

[0046] The printing operation of the electrophotographic device will be described below. FIG. 3 is a schematic cross-sectional view of an example of an electrophotographic device according to an embodiment of the present disclosure. The photoconductor 18 rotates in the direction of the arrow and is uniformly charged by a charging roller 24 for charging the photoconductor 18. Then, an electrostatic latent image is formed on the surface of the photoconductor 18 by a laser beam 23, which is an exposure means. The electrostatic latent image is visualized as a toner image by the application of toner 15 by a developing device 22 arranged in contact with the photoconductor 18 (development). The development is a so-called reversal development in which a toner image is formed on the exposed portion. The toner image formed on the photoconductor 18 is transferred to paper 34, which is a recording medium, by a transfer roller 29, which is a transfer member. The paper 34 is fed into the device via a paper feed roller 35 and an adsorption roller 36, and is transported between the photoconductor 18 and the transfer roller 29 by an endless belt-like transfer transport belt 32. The transfer transport belt 32 is driven by a driven roller 33, a drive roller 28, and a tension roller 31. A voltage is applied to the transfer roller 29 and the attraction roller 36 from a bias power supply 30. The paper 34 onto which the toner image has been transferred is fixed by a fixing device 27 and then ejected outside the device, completing the printing operation. Meanwhile, residual toner that has not been transferred and remains on the photoconductor 18 is scraped off by a cleaning blade 26, which is a cleaning member for cleaning the photoconductor surface, and stored in a waste toner storage container 25. The cleaned photoconductor 18 repeats the above printing operation.

[0047] <<Process cartridge>> The electrophotographic member according to the present disclosure can be suitably used as a developing member such as a developer carrier in a process cartridge, a developer supplying / stripping member, and a developer regulating member. EXAMPLES

[0048] The present disclosure will be described in detail below with reference to specific examples, but the technical scope of the present invention is not limited to these. <<Raw material preparation>> <Polymerizable monomer: synthesis of polyether monoacrylate> First, polyether acrylates that form the structure represented by formula (1) were synthesized. A synthesis example of a polyether monoacrylate that can form the structure represented by formula (1) will be shown below. (Polyether monoacrylate A-1) 15.5 parts by mass of 1-hexanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were placed in an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 1041 parts by mass of a gas mixture of ethylene oxide / propylene oxide in a molar fraction of 8:2 was added under a pressure inside the vessel of approximately 0.5 M. Pa, and continuously introduced over 260 minutes. While maintaining the temperature at 100 ° C, the reaction was carried out for 180 minutes until the pressure inside the vessel was 0.2 MPa or less. After that, the temperature was raised to 130 ° C over 30 minutes, and stirring was carried out until the change in the pressure inside the vessel was 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and after stirring at 90 ° C for 30 minutes, 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. Next, the alkali adsorbent was removed by filtration, and dried under reduced pressure at 130 ° C to obtain a polyether monool of Mn 6000.

[0049] Next, 100 parts by mass of the obtained polyether monol, 1.26 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.02 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature and washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-1.

[0050] (Polyether monoacrylate A-2) 18.6 parts by mass of 1-hexanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure in the system was reduced to -0.1 MPa at 100°C, and 976 parts by mass of a gas mixture of ethylene oxide / propylene oxide = 95:5 in molar fraction was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 180 minutes until the pressure inside the container became 0.2 MPa or less. After that, the temperature was raised to 130°C over 30 minutes, and stirring was carried out until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90° C. for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. The alkali adsorbent was then removed by filtration, and the mixture was dried under reduced pressure at 130° C. to obtain a polyether monool having Mn of 5000.

[0051] Next, 100 parts by mass of the obtained polyether monol, 1.51 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 2.42 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.08 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 5 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-2.

[0052] (Polyether monoacrylate A-3) Polyether monoacrylate A-3 was obtained in the same manner as in the preparation of polyether monoacrylate A-2, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 8:2.

[0053] (Polyether monoacrylate A-4) 33.7 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Laboratory Co., Ltd.) were placed in an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 984 parts by mass of a gas mixture of ethylene oxide / propylene oxide at a molar fraction of 8:2 was continuously introduced over 240 minutes while maintaining the pressure inside the vessel at approximately 0.5 MPa. While maintaining the temperature at 100°C, the vessel was The reaction was continued for 150 minutes until the internal pressure was 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in the internal pressure of the container was 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (manufactured by Kyowa Chemical Industry Co., Ltd.) was added and stirred for another 30 minutes. Next, the alkali adsorbent was removed by filtration, and the mixture was dried under reduced pressure at 130°C to obtain a polyether monool having Mn2000.

[0054] Next, 100 parts by mass of the obtained polyether monol, 3.78 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 6.05 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-4.

[0055] (Polyether monoacrylate A-5) 67.4 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 946 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 130 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 1000.

[0056] Next, 100 parts by mass of the obtained polyether monol, 7.56 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 12.1 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-5.

[0057] (Polyether monoacrylate A-6) 112 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 5 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 937 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 240 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 120 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 600.

[0058] Next, 100 parts by mass of the obtained polyether monol, 12.6 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 20.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-6.

[0059] (Polyether monoacrylate A-7) 169 parts by mass of 1-butanol (Tokyo Chemical Industry Co., Ltd.) and 8 parts by mass of potassium hydroxide (Kojundo Chemical Research Institute Co., Ltd.) were put into an autoclave and stirred under reduced pressure at 120°C to dissolve and dehydrate. Next, the pressure inside the system was reduced to -0.1 MPa at 100°C, and 927 parts by mass of a gas mixed at a molar fraction of ethylene oxide / propylene oxide = 8:2 was continuously introduced over 220 minutes while maintaining the pressure inside the container at about 0.5 MPa. While maintaining the temperature at 100°C, the reaction was carried out for 120 minutes until the pressure inside the container became 0.2 MPa or less. The temperature was then raised to 130°C over 30 minutes, and the mixture was stirred until the change in pressure inside the container became 0.01 MPa / 30 minutes. 20 parts by mass of pure water was added to the obtained polymer, and the mixture was stirred at 90°C for 30 minutes, after which 50 g of an alkali adsorbent Kyoward 600 (Kyowa Chemical Industry Co., Ltd.) was added and the mixture was stirred for another 30 minutes. Next, the alkaline adsorbent was removed by filtration, and the residue was dried under reduced pressure at 130°C to obtain a polyether monol having Mn of 400.

[0060] Next, 100 parts by mass of the obtained polyether monol, 18.9 parts by mass of acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), 24.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the washed reaction solution, and the solvent was distilled off under reduced pressure to obtain polyether monoacrylate A-7.

[0061] (Polyether monoacrylate A-8) Polyether monoacrylate A-8 was obtained in the same manner as in the preparation of polyether monoacrylate A-5, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 9:1.

[0062] (Polyether monoacrylate A-9) Polyether monoacrylate A-9 was obtained in the same manner as in the preparation of Polyether monoacrylate A-5, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5.

[0063] (Polyether monomethacrylate A-10) A polyether monool having Mn 600 was obtained in the same manner as in the preparation of polyether monoacrylate A-6, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5. Next, 100 parts by mass of the obtained polyether monool, 15.0 parts by mass of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 20.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C, and the reaction was carried out. The reaction was carried out for 6 hours while removing the water produced from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of a 5% aqueous sodium hydroxide solution, and further washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monomethacrylate A-10.

[0064] (Polyether monomethacrylate A-11) A polyether monool having Mn 400 was obtained in the same manner as in the preparation of polyether monoacrylate A-7, except that the molar fraction of the ethylene oxide / propylene oxide mixed gas was changed to 5:5. Next, 100 parts by mass of the obtained polyether monol, 22.6 parts by mass of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 24.2 parts by mass of paratoluenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.11 parts by mass of hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd.), and 250 ml of toluene were charged into a Dean-Stark reactor equipped with a stirrer. The mixture was heated and stirred at 115°C and reacted for 6 hours while removing water generated by the reaction from the system. The reaction solution was then cooled to room temperature, washed twice with 120 g of 5% aqueous sodium hydroxide solution, and then washed three times with 120 g of pure water. The organic phase was separated from the reaction solution after washing, and the solvent was distilled off under reduced pressure to obtain polyether monomethacrylate A-11. The obtained polyether mono(meth)acrylates are shown in Table 1.

[0065] [Table 1] The polyether composition ratio is expressed as a mole fraction. EO represents ethylene oxide, and PO represents propylene oxide.

[0066] <Polymerizable monomers: synthesis of ionic compounds> Next, ionic compounds that form a structure represented by formula (2) were synthesized. Synthesis examples of ionic compounds that can form a structure represented by formula (2) are shown below. (Synthesis of ionic compound C-1) 15.0 g (0.06 mol) of potassium 3-sulfopropyl methacrylate (Tokyo Chemical Industry Co., Ltd.) was suspended in 100 mL of tetrahydrofuran and 0.5 mL of N,N-dimethylformamide, then 20 mL (0.28 mol) of thionyl chloride was added and stirred for 3 hours. This was concentrated under reduced pressure, and the residue was dissolved in dichloromethane, washed with 50 mL of pure water and 50 mL of saline, and concentrated under reduced pressure again to obtain a pale yellow liquid. The resulting pale yellow liquid was added to a solution of 9.20 g (0.06 mol) of trifluoromethanesulfonylimide (Tokyo Chemical Industry Co., Ltd.) and 27.3 mL (0.20 mol) of triethylamine (Kishida Chemical Co., Ltd.) dissolved in 50 mL of tetrahydrofuran, stirred for 2 hours, and then the reaction solution was concentrated under reduced pressure. The resulting residue was dissolved in dichloromethane, washed with 150 mL of pure water, and the organic layer was dried under reduced pressure. A yellow liquid is obtained by dissolving the obtained yellow liquid in 300 mL of tetrahydrofuran, adding 1.43 g (0.18 mol) of lithium hydride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and stirring overnight. After filtering off the unreacted lithium hydride using Celite filtration, the filtrate is dried under reduced pressure to obtain ionic compound C-1.

[0067] (Synthesis of ionic compound C-2) Ion compound C-2 was obtained in the same manner as for ionic compound C-1, except that the starting material was changed to 15.9 g (0.06 mol) of 3-sulfopropyl acrylate potassium salt (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0068] (Synthesis of ionic compound C-3) Hydroxymethanesulfonate(Atomax Chemical 7.78 g (0.07 mol) of methacrylic acid (manufactured by Kishida Chemical Co., Ltd.) was dissolved in 50 mL of tetrahydrofuran, 5.17 g (0.06 mol) of methacrylic acid (manufactured by Kishida Chemical Co., Ltd.) and molecular sieves were added, and the mixture was stirred at 80°C for 3 hours. The filtrate was filtered through Celite and dried under reduced pressure, and then dissolved again in 50 mL of THF, and 2.41 g (0.06 mol) of potassium hydride (manufactured by Merck) was added and stirred at room temperature for 2 hours. The white solid obtained after drying under reduced pressure was used as the starting material to obtain ionic compound C-3 in the same manner as ionic compound C-1.

[0069] (Synthesis of ionic compound C-4) 1-HEPTANESULFONYL CHLORIDE, 7-HYDROXY (Hong Kong Chemhere Product) 12.9g and triethylamine 6.07g (0.06mol) of sodium acrylate (Kishida Chemical Co., Ltd.) was added to 80mL of dichloromethane and stirred at room temperature. After washing with 100mL of pure water, the organic phase was dried under reduced pressure to obtain an oily liquid. 5.64g (0.06mol) of sodium acrylate (Merck Co., Ltd.) was dissolved in 50mL of ethanol, and the oily liquid obtained earlier and 0.022g (0.20mmol) of hydroquinone (Kanto Chemical Co., Ltd.) were added and stirred at 70°C for 5 hours. The pale yellow solid obtained after drying under reduced pressure was used as the starting material to obtain ionic compound C-4 in the same manner as ionic compound C-2.

[0070] (Synthesis of ionic compound C-5) Ion compound C-5 was obtained in the same manner as for ionic compound C-2, except that the reactant was changed from trifluoromethanesulfonamide (Tokyo Chemical Industry Co., Ltd.) to 5.94 g (0.06 mol) of sulfamoyl fluoride (Atomax Chemicals Products).

[0071] (Synthesis of ionic compound C-6) Ionic compound C-6 was obtained in the same manner as for ionic compound C-1, except that the reactant was changed from trifluoromethanesulfonamide (Tokyo Chemical Industry Co., Ltd.) to 18.0 g (0.06 mol) of nonafluorobutane-1-sulfonamide (Enamine Co., Ltd.).

[0072] (Synthesis of ionic compound C-7) Ion compound C-7 was obtained in the same manner as ionic compound C-5, except that lithium hydride was changed to 4.32 g (0.18 mol) of sodium hydride (manufactured by Tokyo Chemical Industry Co., Ltd.) as the reactant.

[0073] (Synthesis of ionic compound C-8) Ion compound C-8 was obtained in the same manner as ionic compound C-6, except that lithium hydride was changed to 7.22 g (0.18 mol) of potassium hydride (Merck) as the reactant. The chemical structures of the obtained reactive ion compounds are shown in Formulas C-1 to C-8. [ka] [ka]

[0074] <Synthesis of acrylic sulfonylimide conductive agent> (Acrylsulfonylimide Conductive Agent IP-1) Into a four-neck separable flask equipped with a stirrer, a condenser, a thermometer, and a nitrogen inlet tube, 50.0 parts by mass of M-230G (product name, chemical structure: monofunctional methoxypolyalkylene glycol methacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) as a polymerizable monomer that gives the structural unit (1), 10.0 parts by mass of C-3 as a polymerizable monomer that gives the structural unit (2), 1.0 L of dried ethanol, 1.0 L of 2,2'-azobisisobutyronitrile (manufactured by Tokyo Chemical Industry Co., Ltd.), and The mixture was stirred until the system was homogenized. While stirring, the temperature in the reaction system was raised to 70°C, and the reaction was carried out for 8 hours under nitrogen reflux. After that, the ethanol was distilled off to obtain the copolymer acrylic sulfonylimide conductive agent IP-1.

[0075] (Acrylsulfonylimide conductive agents IP-2 to IP-27 and IPH-1 to IPH-3) The synthesis of acrylic sulfonylimide conductive agents IP-2 to IP-27 and IPH-1 to IP-27 was carried out in the same manner as in the synthesis of IP-1, except that the polymerizable monomer and its blending amount were changed to the conditions shown in Table 2. I got IPH-3.

[0076] [Table 2] The materials used in the table are as follows: M-230G (product name, chemical structure: monofunctional methoxypolyalkylene glycol methacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) AM-130G (product name, chemical structure: monofunctional methoxypolyalkylene glycol acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) AM-230G (product name, chemical structure: monofunctional methoxypolyalkylene glycol acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) AM-90G (product name, chemical structure: monofunctional methoxy polyalkylene glycol acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-450G (product name, chemical structure: monofunctional methoxypolyalkylene glycol methacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.) M-40G (product name, chemical structure: monofunctional methoxypolyalkylene glycol methacrylate) (Manufactured by Shin-Nakamura Chemical Co., Ltd.) Non-ether structure AA (product name: IBOA-B, chemical structure: monofunctional isobornyl acrylate (structure shown in formula (4) below), manufactured by Daicel Corporation) Formula (4) [ka]

[0077] The structures of the materials used when polymerized are as follows: M-230G (methoxypolyethylene glycol methacrylate, R in formula (1-1) 1 : Methyl group, R 2 : Ethylene group -(CH2)2-, R 3 : methyl group, m1: 23, n1: 0, Mn: 1000) AM-130G (methoxypolyethylene glycol #600 acrylate, R in formula (1-1) 1 : Hydrogen atom, R 2 : Ethylene group, R 3 : methyl group, m1: 13, n1: 0, Mn: 650) AM-230G (methoxypolyethylene glycol #1000 acrylate, R in formula (1-1) 1 : Hydrogen atom, R 2 : Ethylene group, R 3 : methyl group, m1: 23, n1: 0, Mn: 1000) AM-90G (methoxypolyethylene glycol #400 acrylate, R in formula (1-1) 1 : Hydrogen atom, R 2 : Ethylene group, R 3 : methyl group, m1:9, n1:0, Mn:500) M-450G (methoxypolyethylene glycol methacrylate, R in formula (1-1) 1 : Methyl group, R 2 : Ethylene group, R 3 : methyl group, m1: 45, n1: 0, Mn: 2000) M-40G (methoxypolyethylene glycol methacrylate, R in formula (1-1) 1 : Methyl group, R 2 : Ethylene group, R 3 : methyl group, m1:3, n1:0, Mn:300)

[0078] <Synthesis of isocyanate-terminated prepolymer> An isocyanate compound for forming a urethane resin was synthesized. (Synthesis of isocyanate-terminated prepolymer B-1) In a nitrogen atmosphere, 33.8 parts by mass of polymeric MDI (trade name: Millionate MR; manufactured by Tosoh Corporation) and 100.0 parts by mass of polypropylene glycol-based polyol (trade name: Exenol 230; manufactured by Asahi Glass Co., Ltd.) were mixed in a reaction vessel while maintaining the temperature inside the reaction vessel at 65°C. Then, it was gradually added dropwise. After the dropwise addition, the mixture was reacted at 65°C for 2 hours, and 57.3 parts by mass of methyl ethyl ketone was added. The resulting reaction mixture was cooled to room temperature and the isocyanate group content was 4.80% by weight. Thus, an isocyanate group-terminated urethane prepolymer B-1 was obtained.

[0079] (Synthesis of isocyanate-terminated prepolymer B-2) In a nitrogen atmosphere, 8.8 parts by mass of polymeric MDI (trade name: Millionate MT; manufactured by Tosoh Corporation) was dissolved in methyl ethyl ketone in a reaction vessel so that the final solid content was 50%. Then, while maintaining the temperature in the reaction vessel at 65°C, 100.0 parts by mass of olefin A polyol (product name: Poly bd R-45HT; manufactured by Idemitsu Kosan Co., Ltd.) was gradually added dropwise to the reaction vessel. After the dropwise addition was completed, the mixture was reacted for 2 hours at 65° C. The resulting reaction mixture was cooled to room temperature to obtain an isocyanate-terminated prepolymer B-2 having a solid content of 50% and an isocyanate group content of 1.40% by weight.

[0080] <<Preparation of paint for forming surface layer>> (Preparation of Surface Layer Forming Paint E-1) As the material for the surface layer, the materials shown in Table 3 below were mixed with stirring. Next, methyl ethyl ketone was added so that the total solid content ratio became 30% by mass, and then mixed with a sand mill. Next, the viscosity was further adjusted to 10 to 13 cps with methyl ethyl ketone to prepare a surface layer forming coating material E-1.

[0081] [Table 3]

[0082] (Preparation of Surface Layer Forming Paint E'-1) As the surface layer material, the materials shown in Table 4 below were mixed with stirring, and a surface layer forming paint E'-1 was obtained in the same manner as E-1.

[0083] [Table 4]

[0084] (Preparation of Surface Layer Forming Paints E-2 to E-27 and EH-1 to EH-4) Except for changing the acrylic sulfonylimide conductive agent as shown in Table 5 below, the same procedure as for the surface layer forming paint E-1 was performed to obtain surface layer forming paints E-2 to E-27 and EH-1 to EH-4.

[0085] [Table 5] In Table 5, Li·TFSI represents lithium bis(trifluoromethanesulfonyl)imide (the same applies below).

[0086] <<Making a conductive roller>> <Preparation of Silicone Rubber Elastic Roller> As a conductive substrate, a core wire made of SUS304 with an outer diameter of 6 mm and a length of 264 mm was coated with a primer (product name: DY35-051, manufactured by Toray Dow Corning Co., Ltd.) and heated at 150 °C for 20 minutes. This conductive substrate was placed concentrically in a cylindrical mold with an inner diameter of 11.5 mm. As the material for the elastic layer, an addition-type silicone rubber composition obtained by mixing the materials shown in Table 6 below with Trimix (product name: TX-15, manufactured by Inoue Manufacturing Co., Ltd.) was injected into a mold heated to 115 °C. After injecting the material, it was heated and molded at 120 °C for 10 minutes, cooled to room temperature, and then demolded from the mold to obtain an elastic roller D'-1 with an intermediate layer having a thickness of 2.71 mm formed on the outer periphery of the conductive base material.

[0087]

Table 6

[0088] <Fabrication of NBR rubber elastic roller> Each material of the types and amounts shown in Table 7 below was mixed with a pressure kneader to obtain a kneaded rubber composition A.

[0089]

Table 7

[0090]

Table 8

[0091] Next, a crosshead extruder having a mechanism for feeding a conductive mandrel and a mechanism for discharging an unvulcanized rubber roller was prepared, and a die with an inner diameter of 16.5 mm was attached to the crosshead, and the crosshead extruder was adjusted to 80°C and the conveying speed of the conductive mandrel was adjusted to 60 mm / sec. Under these conditions, an unvulcanized rubber composition was fed from the extruder, and the unvulcanized rubber composition was coated as an unvulcanized rubber layer on the circumferential surface of the conductive mandrel prepared above in the crosshead to obtain an unvulcanized rubber roller. Next, the unvulcanized rubber roller was placed in a hot air vulcanizing furnace at 170°C and heated for 60 minutes to obtain an unpolished conductive roller. Then, the end of the NBR rubber elastic layer where the unvulcanized rubber layer was vulcanized was cut and removed, and the surface of the NBR rubber elastic layer was polished with a rotating grindstone. As a result, an elastic roller D'-2 was produced with a diameter of 8.4 mm at each position 90 mm from the center to both ends and a central diameter of 8.5 mm.

[0092] <Example 1> First, the elastic roller D'-1 prepared above was immersed in the above-mentioned surface layer forming paint E-1 to form a coating film of the paint on the surface of the elastic layer, and then air-dried. A surface layer having a thickness of about 15 μm was provided on the outer periphery of the elastic layer by heat treatment, thereby producing a conductive roller, which was a conductive roller D-1 used in Example 1.

[0093] <Examples 2 to 29 and Comparative Examples 1 to 5> Except for using the paint for forming the surface layer shown in Table 9, a coating film was formed on the surface of the elastic layer of the elastic roller D'-1 in the same manner as in Example 1, dried, and then heat-treated at a temperature of 150°C for 1 hour to obtain conductive rollers D-2 to D-29 of Examples 2 to 29 and conductive rollers DH-1 to 5 of Comparative Examples 1 to 4.

[0094] <Example 30 and Comparative Example 6> Except for using the surface layer-forming paint shown in Table 9 and using elastic roller D'-2, the conductive roller D-30 of Example 30 and the conductive roller DH-6 of Comparative Example 6 were obtained by the same operations as in Examples 2 to 29 and Comparative Examples 1 to 5 above.

[0095] <Confirmation of the structure of the product> The resin obtained in this synthesis example was analyzed using a pyrolysis apparatus (trade name: Pyrofoil Sampler JPS-700, manufactured by Japan Analytical Industry Co., Ltd.) and a GC / MS apparatus (trade name: FocusGC / ISQ, manufactured by Thermo Fisher Scientific Co., Ltd.) at a pyrolysis temperature of 590°C and helium as a carrier gas. As a result, it was confirmed from the obtained fragment peaks that the resin had the structures of structural formulas (1) and (2).

[0096] <<Evaluation of conductive rollers>> The details of the conductive rollers according to the examples and comparative examples are shown in Table 9 below.

[0097] [Table 9] The conductive rollers according to the examples thus obtained were evaluated for the following items. The results are shown in Table 10.

[0098] <Evaluation of Roller Resistance Fluctuations> The roller resistance value was measured using a conductive roller that had been left in an environment of 0° C. for 6 hours or more. [Measurement of initial roller resistance] FIG. 4 shows a schematic diagram of a roller resistance fluctuation evaluation jig according to the present disclosure. In FIG. 4(a), in an environment of 0° C., a cylindrical metal 37 with a diameter of 24 mm is rotated at a surface speed of 50 mm / sec while pressing both ends of a conductive shaft body 42 with a load of 4.9 N each via a conductive bearing 38, and a conductive roller 41 is driven by the rotation. Next, in FIG. 4(b), a voltage of 50 V is applied by a high-voltage power source 39, and the potential difference between both ends of a resistor with a known electrical resistance (whose electrical resistance is two or more orders of magnitude lower than that of the conductive roller) arranged between the cylindrical metal 37 and ground is measured. To measure the potential difference, a voltmeter 40 (FLUKE 189TRUE R The measured potential difference and the electrical resistance of the resistor were used to calculate the conductivity. The current flowing through the cylindrical metal via the conductive roller 41 was calculated. The electrical resistance of the conductive roller 41 was calculated by dividing the applied voltage of 50 V by the obtained current. Here, the potential difference was measured by sampling for 3 seconds starting 2 seconds after the voltage was applied, and the value calculated from the average value was regarded as the initial roller resistance value.

[0099] [Measurement of roller resistance after evaluation] Immediately after the ghost evaluation described below was carried out, the roller was taken out and the roller resistance after energization was measured in an environment of 0°C.

[0100] [Electrical Deterioration] The value obtained by dividing the roller resistance value after evaluation by the initial roller resistance value (roller resistance value after evaluation / initial roller resistance value) was used as an index of electrical deterioration.

[0101] <Ghost Rating> Next, the conductive roller whose initial roller resistance had been measured as described above was left in an environment of 0° C. for 6 hours or more, and then the following evaluation was performed. A laser printer (product name: LBP7700C; manufactured by Canon Inc.) having the configuration shown in FIG. 3 was placed in an environment of 0° C., and the conductive roller serving as the electrophotographic member of this example was loaded as a developing roller, and ghost images were evaluated. That is, using black toner, a 15 mm square solid black image was printed at the leading edge of each sheet, followed by a full halftone image as an image pattern. Next, the density unevenness appearing in the halftone portion due to the period of the developing roller as a toner carrier was visually evaluated, and ghosting was evaluated according to the following criteria. [Ghost evaluation in 0℃ environment] A: No ghosts are observed at all B: Very slight ghosting is observed. C: Significant ghosting is observed.

[0102] [Table 10] In the table, "E+number" is the exponential notation of a number. For example, "5.4E+05" is "5.4×10 5 " (and so on).

[0103] <Horizontal streak image evaluation> Next, the obtained electrophotographic members according to Examples 29 and 30 and Comparative Example 6 were subjected to the above-mentioned evaluation of the roller resistance value fluctuation, and were also used as charging rollers to perform evaluation of the following items. A change in the conductivity of the charging roller (an increase in electrical resistance) caused by energization of the charging roller can cause fine streak-like uneven density (horizontal streaks) in a halftone image. This is called a horizontal streak image. The more the conductivity of the charging roller changes, the more this horizontal streak image tends to occur, and it tends to become more noticeable with long-term use of the electrophotographic device. The electrophotographic member of the present disclosure was incorporated into the electrophotographic device as a charging roller, and the following evaluations were performed.

[0104] An electrophotographic laser printer (product name: HPColor L) As a charging roller, the HP Serjet Enterprise CP4515dn The conductive rollers obtained in Examples 29 and 30 and Comparative Example 6 were attached to the rollers. A durability test was then carried out in which images with a print density of 4% (images in which horizontal lines with a width of 2 dots and an interval of 50 dots were drawn in the direction perpendicular to the rotational direction of the photoconductor) were continuously output. In addition, after the continuous output of 24,000 sheets of images, a halftone image (images in which horizontal lines with a width of 1 dot and an interval of 2 dots were drawn in the direction perpendicular to the rotational direction of the photoconductor) was output for image checking. The obtained images were visually observed, and fine streak-like density unevenness (horizontal streaks) was evaluated. The evaluation results are shown in Table 11. A: A level where no horizontal streaks occur at all. B: Horizontal streaks are slightly observed only at the edges of the image. C: Horizontal lines occur in almost half of the image, and are noticeable.

[0105] [Table 11]

[0106] <Considerations of evaluation results> The electrophotographic members prepared in Examples 1 to 30 contain the compounds having structures represented by formulas (1) and (2) according to the present disclosure in the surface layer serving as the conductive layer according to the present disclosure, and therefore show little increase in resistance after image output in a 0°C environment, and maintain good image quality. In contrast, in Comparative Examples 1 to 6, which do not contain compounds having structures represented by formulas (1) and (2) according to the present disclosure, the resistance increases significantly before and after image output under the above environment, and significant problems occur in image evaluation.

[0107] <<Fabrication of blade components>> <Example 31> FIG. 6 shows a cross-sectional view of the electrophotographic member produced in this embodiment. As the substrate 51, a SUS sheet (manufactured by Nisshin Steel Co., Ltd.) having a thickness of 0.08 mm was press-cut to a dimension of 200 mm in length and 23 mm in width. Next, the cut SUS sheet was immersed in the paint E-1 for forming a surface layer so that the length 53 from the longitudinal end of the cut SUS sheet was 1.5 mm, a coating film of the paint was formed, and the sheet was dried. Further, by heating at a temperature of 140° C. for 1 hour, a resin layer 52 having a film thickness 54 of 10 μm was provided on the surface of the longitudinal end of the SUS sheet, and a blade member (developing blade) was produced as an electrophotographic member according to the present disclosure.

[0108] <Example 32> A blade member of Example 32 was produced in the same manner as in Example 31, except that the coating material for forming the surface layer was changed from E-1 to E-25.

[0109] <Comparative Example 7> A blade member of Comparative Example 7 was produced in the same manner as in Example 31, except that the coating material for forming the surface layer was changed from E-1 to EH-2.

[0110] <<Evaluation of blade components>> <Evaluation of electrical resistance> The electrical resistance values ​​of the blade members according to Examples 31 and 32 and Comparative Example 7 were measured in the same manner as the resistance measurement of the roller described above. However, the roller-shaped electrophotographic member 1 in Fig. 4(a) was replaced by the blade member shown in Fig. 6. Specifically, the bearings 38 were brought into contact with both longitudinal ends of the base 51 of the blade member shown in Fig. 6, and a load of 1.0 N was applied to each end, so that the resin layer at the tip of the blade member was brought into contact with the peripheral surface of the cylindrical metal 37 perpendicularly. Next, without rotating the cylindrical metal 37, a voltage of 50 V was applied by a high-voltage power supply 39, and the potential difference between both ends of a resistor having a known electrical resistance (an electrical resistance two or more orders of magnitude lower than the electrical resistance of the electrophotographic member 1) disposed between the cylindrical metal 37 and the ground was measured. From the measured potential difference and the electrical resistance of the resistor, the current flowing through the cylindrical metal 37 via the developing blade was calculated. The applied voltage of 50 V was divided by the obtained current to determine the electrical resistance value of the electrophotographic member 1. Here, the potential difference was measured by sampling for 3 seconds starting 2 seconds after the voltage was applied, and the value calculated from the average value was regarded as the resistance value.

[0111] <Regulatory Unfavorable Evaluation> The electrophotographic member to be evaluated was loaded as a developing blade into a laser printer (product name: LBP7700C; manufactured by Canon Inc.) having the configuration shown in FIG. 3. The laser printer was placed in a 0° C. environment and left for at least 2 hours, after which 100 black images with a printing rate of 1% were continuously output. Then, a solid white image was output onto a new copy paper. After outputting these images, the state of the toner coat on the surface of the developing member was observed, and the presence or absence of electrostatic toner aggregation (regulation failure) due to abnormal charging of the toner was visually observed. The observation results were evaluated according to the following criteria. A: There is no regulation defect on the toner coat. B: There is a regulation defect on the toner coat, but it does not appear in the image. C: Poor regulation appears in the image.

[0112] [Table 12]

[0113] <Considerations of evaluation results> In Examples 31 and 32, the surface layer as the conductive layer according to the present disclosure contains the compounds having the structures represented by formulas (1) and (2) according to the present disclosure, so that an increase in resistance value was not observed in a 0°C environment, and no regulation failure occurred. On the other hand, in Comparative Example 7, an increase in resistance value was observed, and regulation failure occurred. It is considered that the regulation failure in a 0°C environment occurred as a result of the development blade resistance increasing, the blade bias not being applied to the specified value, and the toner being charged non-uniformly.

[0114] <<Preparation of the toner supply roller>> <Example 33> A stainless steel (SUS304) core bar having a diameter of 5 mm was placed in a mold as a substrate, and a urethane rubber composition obtained by mixing the following materials was injected into a cavity formed in the mold. Conductive agent IP-1: 2.0 parts by weight Polyol Kuraray Polyol C-3090 (trade name, manufactured by Kuraray Co., Ltd.): 84.2 parts by mass Polyol Kuraray Polyol F-2010 (trade name, manufactured by Kuraray Co., Ltd.): 18.6 parts by mass Isocyanate (trade name: Cosmonate TM20; manufactured by Mitsui Chemicals Co., Ltd.): 22.7 parts by mass Silicone foam stabilizer (product name: SRX274C, manufactured by Toray Dow Corning Silicones): 1.0 part by mass Amine catalyst (product name: TOYOCAT-ET, manufactured by Tosoh Corporation): 0.3 parts by weight Amine catalyst (product name: TOYOCAT-L33, manufactured by Tosoh Corporation): 0.2 parts by weight ·Water: 2.0 parts by mass The mold was then heated to vulcanize and foam-cure the urethane rubber composition at a temperature of 50° C. for 20 minutes, and the base having a polyurethane foam layer formed on its periphery was removed from the mold. In this way, a toner supply roller according to Example 31 was produced, which had a polyurethane foam layer with a diameter of 16.1 mm on the periphery of the base.

[0115] <Example 34> A toner supply roller according to Example 34 was produced in the same manner as in Example 33, except that the conductive agent was changed from 2.0 parts by mass of IP-1 to 6.0 parts by mass of IP-25.

[0116] <Comparative Example 8> The conductive agent was changed from 2.0 parts by mass of IP-1 to 0.3 parts by mass of Li TFSI. In the same manner as in Example 31, a toner supply roller according to Comparative Example 8 was produced.

[0117] <<Evaluation of the toner supply roller>> <Resistance measurement> The electrical resistance values ​​of the toner supply rollers according to Examples 33 and 34 and Comparative Example 8 were measured in the same manner as in the resistance measurement of the conductive roller described above, except that the load applied to both ends of the substrate was 2.5 N, and the roller rotation speed during measurement was 32 rpm.

[0118] <Regulatory Unfavorable Evaluation> The toner supply rollers of Example 31 and Comparative Example 8 were loaded into a process cartridge for a laser printer (product name: LBP7700C, manufactured by Canon Inc.) having the configuration shown in FIG. 2. The process cartridge was then assembled into the laser printer, placed in a 0°C environment, and left for 6 hours. Next, 100 black images with a printing rate of 1% were output continuously. Then, a solid white image was output on a new copy paper. After outputting these images, the state of the toner coat on the surface of the developing blade was observed, and the presence or absence of electrostatic toner aggregation (regulation failure) due to abnormal charging of the toner was visually observed. The evaluation criteria for the regulation failure evaluation are as follows. Note that when regulation failure occurs, image problems such as spotted unevenness in non-printed areas and toner lumps on the image may occur. Rank A: No regulation defect exists on the toner coat. Rank B: A regulation defect exists on the toner coat, but does not appear in the image. Rank C: Poor regulation appears in the image.

[0119] [Table 13]

[0120] <Discussion of Results> In Examples 33 and 34, the surface layer as the conductive layer according to the present disclosure is formed by adding the compound represented by the formula (1) and Since the toner supply roller contains a compound having a structure represented by (1) and (2), no increase in resistance was observed in a 0°C environment, and no regulation failure occurred. On the other hand, in Comparative Example 8, an increase in resistance was observed, and regulation failure occurred. It is considered that the regulation failure in a 0°C environment occurred as a result of the resistance of the toner supply roller increasing, and the toner on the developing roller not being properly scraped off by the toner supply roller, resulting in an excess of toner supply.

[0121] The present disclosure includes the following configurations. (Configuration 1) 1. An electrophotographic member having an electrically conductive substrate and an electrically conductive layer on the substrate, The electrophotographic member, wherein the conductive layer contains a compound having a structure represented by the following formula (1) and a structure represented by the following formula (2): [ka] [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, A1 represents a linking group having a structure represented by (-CH2CH2-O-). In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms, R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms, X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. (Configuration 2) 2. The electrophotographic member according to claim 1, wherein A1 further has a structure represented by (-CH2CH(CH3)-O-). (Configuration 3) The structure represented by the formula (1) is a structure represented by the following formula (1-1): 3. The electrophotographic member according to claim 1 or 2: [ka] R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R3 represents an alkyl group having 1 to 6 carbon atoms, m1 and n1 are the average number of moles added, where m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. However, the arrangement of the structure represented by (-CH2-CH2-O-) and the structure represented by (-CH2-CH(CH3)-O-) may be a block copolymer or a random copolymer. (Configuration 4) 4. The electrophotographic member according to any one of configurations 1 to 3, wherein the conductive layer contains a copolymer having a structure represented by formula (1) and a structure represented by formula (2). (Configuration 5) 5. The electrophotographic member according to any one of configurations 1 to 4, wherein the copolymer has a number average molecular weight (Mn) of 500 to 100,000. (Configuration 6) the conductive layer contains the copolymer and a binder resin, 6. The electrophotographic member according to any one of configurations 1 to 5, wherein the binder resin contains an ether structure in the molecule. (Configuration 7) 7. The electrophotographic member of embodiment 6, wherein the binder resin is a polyurethane. (Configuration 8) 8. An electrophotographic process cartridge configured to be detachably mountable to a main body of an electrophotographic apparatus, comprising the electrophotographic member according to any one of configurations 1 to 7. (Configuration 9) 9. The electrophotographic process cartridge according to configuration 8, comprising the electrophotographic member as a developing member. (Configuration 10) An electrophotographic image forming apparatus comprising the electrophotographic member according to any one of Configurations 1 to 7 as a developing member. (Configuration 11) A copolymer having a structure represented by the following formula (1) and a structure represented by the following formula (2): [ka] [ka] (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, A1 represents a linking group having a structure represented by (-CH2CH2-O-). In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms, R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms, X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion. (Configuration 12) 12. The copolymer according to claim 11, wherein A1 further has a structure represented by (-CH2CH(CH3)-O-). (Configuration 13) The copolymer according to aspect 11 or 12, wherein the structure represented by formula (1) is a structure represented by formula (1-1): [ka] R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, m1 and n1 are the average number of moles added, where m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. However, the arrangement of the structure represented by (-CH2-CH2-O-) and the structure represented by (-CH2-CH(CH3)-O-) may be a block copolymer or a random copolymer. (Configuration 14) 14. The copolymer according to any one of aspects 11 to 13, wherein the copolymer has a number average molecular weight (Mn) of 500 to 100,000. (Configuration 15) The copolymer according to any one of configurations 11 to 14, wherein the molar ratio of the structure represented by formula (1) to the structure represented by formula (2) (formula (1):formula (2)) is 60:40 to 95:5. . [Explanation of symbols]

[0122] 1: electrophotographic member, 2: substrate, 3: surface layer, 4: elastic layer, 5: intermediate layer

Claims

1. 1. An electrophotographic member having an electrically conductive substrate and an electrically conductive layer on the substrate, The electrophotographic member, wherein the conductive layer contains a compound having a structure represented by the following formula (1) and a structure represented by the following formula (2): (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, A1 is (-CH 2 CH 2 It represents a linking group having a structure represented by the formula: In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms, R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms, X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion.

2. The A1 is (-CH 2 CH (CH 3 2. The electrophotographic member of claim 1 further comprising a structure represented by the formula:

3. The structure represented by the formula (1) is a structure represented by the following formula (1-1):

2. The electrophotographic member of claim 1 : R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, m1 and n1 are the average number of moles added, m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. However, (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the structure represented by (a)-(O) may be a block copolymer or a random copolymer.

4. 2. The electrophotographic member of claim 1, wherein the conductive layer comprises a copolymer having a structure represented by formula (1) and a structure represented by formula (2).

5. 5. The electrophotographic member according to claim 4, wherein the number average molecular weight (Mn) of said copolymer is from 500 to 100,000.

6. the conductive layer contains the copolymer and a binder resin, 6. The electrophotographic member according to claim 5, wherein the binder resin contains an ether structure in the molecule.

7. 7. An electrophotographic member according to claim 6 wherein said binder resin is a polyurethane.

8. 8. An electrophotographic process cartridge configured to be detachably mountable to a main body of an electrophotographic apparatus, comprising the electrophotographic member according to claim 1.

9. 9. An electrophotographic process cartridge according to claim 8, comprising the electrophotographic member as a developing member.

10. 8. An electrophotographic image forming apparatus comprising the electrophotographic member according to claim 1 as a developing member.

11. A copolymer having a structure represented by the following formula (1) and a structure represented by the following formula (2): (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, A1 is (-CH 2 CH 2 It represents a linking group having a structure represented by the formula: In formula (2), R 12 represents a hydrogen atom or a methyl group, R 13 represents a linear or branched alkylene group having 1 to 7 carbon atoms, R 14 represents a fluorine atom or a linear or branched perfluoroalkyl group having 1 to 4 carbon atoms, X + represents at least one selected from the group consisting of a lithium ion, a sodium ion, and a potassium ion.

12. The A1 is (-CH 2 CH (CH 3 The copolymer according to claim 11, further having a structure represented by the formula:

13. The copolymer according to claim 11, wherein the structure represented by the formula (1) is a structure represented by the following formula (1-1): R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, R 3 represents an alkyl group having 1 to 6 carbon atoms, m1 and n1 are the average number of moles added, m1 represents an integer of 1 or more, and n1 represents an integer of 0 or more. However, (-CH 2 -CH 2 -O-) and (-CH 2 -CH(CH 3 The arrangement of the structure represented by (a)-(O) may be a block copolymer or a random copolymer.

14. The copolymer according to claim 11, wherein the number average molecular weight (Mn) of the copolymer is 500 to 100,000.

15. The copolymer according to claim 11, wherein the molar ratio of the structure represented by formula (1) to the structure represented by formula (2) (formula (1):formula (2)) is 60:40 to 95:5.

Citation Information

Patent Citations

  • Conductive roller and image forming apparatus equipped with the same

    JP2004163825A